PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA SMAS TARUNA BUMI KHATULISTIWA - Jono, Jono; Aminuyati, Aminuyati; Herkulana, Herkulana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was aimed to determine the effects of learning model’s application Problem Based Learning on students' critical thinking skills on Economics subjects to the Class XI IPS SMAS Taruna Bumi Khatulistiwa. The researcher used experimental method with Quasi-experimental design and quantitative research form. Sample technique used was saturated sampling technique. The data was taken from class XI IPS SMAS Taruna Bumi Khatulistiwa with sample size 24 students in experiment class and 26 students in control class. Data collection techniques used consist of: 1. Observation, 2. Test, and 3. Documentation. Meanwhile, the data collection tool used consist of: 1. Checklist, 2. Test, and 3. Document. The data were obtained from students’ answer sheets in form of description and interview result with Economy teacher of Class XI IPS. Data was processed and be analyzed by statistics. Technique and data analysis used is using t test (independent samples t-test) with error rate 5% (ɑ = 0,05) or 95% confidence level. The result of research showed that there was influence of applying problem based learning model to students' critical thinking ability on Economic lesson of class XI IPS SMAS Taruna Bumi Khatulistiwa. Keywords: Problem Based Learning Model And Critical Thinking Skills